2018
DOI: 10.1074/jbc.m117.795955
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase 6 (HDAC6) deacetylates extracellular signal-regulated kinase 1 (ERK1) and thereby stimulates ERK1 activity

Abstract: Histone deacetylase 6 (HDAC6), a class IIb HDAC, plays an important role in many biological and pathological processes. Previously, we found that ERK1, a downstream kinase in the MAPK signaling pathway, phosphorylates HDAC6, thereby increasing HDAC6-mediated deacetylation of α-tubulin. However, whether HDAC6 reciprocally modulates ERK1 activity is unknown. Here, we report that both ERK1 and 2 are acetylated and that HDAC6 promotes ERK1 activity via deacetylation. Briefly, we found that both ERK1 and 2 physical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 47 publications
(31 reference statements)
2
35
0
1
Order By: Relevance
“…HDAC6 is a class IIb HDAC, which is a key regulator in diversified biological and pathological processes [22]. HDAC6 has been proven to enhance the activity of ERK1/2 through deacetylation, as well as to regulate the oncogenic activity and nuclear localization of mutant K-Ras [22,32].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…HDAC6 is a class IIb HDAC, which is a key regulator in diversified biological and pathological processes [22]. HDAC6 has been proven to enhance the activity of ERK1/2 through deacetylation, as well as to regulate the oncogenic activity and nuclear localization of mutant K-Ras [22,32].…”
Section: Discussionmentioning
confidence: 99%
“…HDAC6 is a class IIb HDAC, which is a key regulator in diversified biological and pathological processes [22]. HDAC6 has been proven to enhance the activity of ERK1/2 through deacetylation, as well as to regulate the oncogenic activity and nuclear localization of mutant K-Ras [22,32]. In terms of cancers, HDAC6 has been regarded as a crucial target of drug development for the treatment of cancers due to its main contribution in oncogenic cell transformation, which is also associated with tumorigenesis and improved survival of cancers [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent insights into the role of HDAC6 in the human (patho)physiology have been significantly advanced by the identification of novel substrates of the enzyme (11)(12)(13)34). However, there is paucity of data mapping substrate specificity and the mechanism of substrate recognition by HDAC6 at the peptide level.…”
Section: Discussionmentioning
confidence: 99%
“…The elevated MAPK phosphatase 1 (MKP1) by HDAC inhibitors was demonstrated to impair self‐renewal, induce differentiation of glioma stem cells and reduce tumorigenesis in vivo (Arrizabalaga et al, ). HDAC6 directly deacetylates ERK1 at lysine 72 for stimulating its activity, which plays an important role in carcinogenesis (Wu et al, ). In this study, we found that HDAC6 inhibition caused a reduction in JNK/c‐Jun activity, preceding its inhibitive effects on glioma growth and invasion.…”
mentioning
confidence: 99%